Heat transfer performance of an oscillating heat pipe under ultrasonic field with dual frequency. Issue 5 (15th January 2015) - Fu, B W; Zhao, N N; Ma, H B; Su, F M
Abstract: The oscillating motion and heat transfer capacity in an oscillating heat pipe (OHP) under the effect of ultrasound was investigated experimentally. Using the electrically- controlled piezoelectric ceramics, the ultrasonic sound was applied to the evaporating section of the OHP. The heat pipe was tested with or without the ultrasonic sound. The effect of ultrasound on the heat transfer performance was conducted with ultrasound of single frequency or dual frequency. The experimental results demonstrate that the OHP under the effect of the ultrasonic sound with dual frequency performs better than that one with single frequency.